A mixed methods study of Black Girls' vulnerability to out-of-school suspensions: The intersection of race and gender. (July 2019) - Gibson, Priscilla; Haight, Wendy; Cho, Minhae; Nashandi, Ndilimeke J.C.; Yoon, Young Ji
Abstract: Although the disproportionate suspension of Black boys has been a longstanding issue, the apparent vulnerability of Black girls to harsh disciplinary practices is of recent concern to educators and researchers (seeCrenshaw, Ocen, & Nanda, 2015 ). We used a sequential (qual → QUANT) mixed methods design to examine the out-of-school suspension (OSS) of Black girls. In-depth, qualitative interviews explored the experiences of 10 Black middle-school girls with OSSs, their caregivers and educators to generate hypotheses for, and then expand, statewide quantitative analyses. Participants described that Black girls were sanctioned more frequently and more harshly than were whites for the same behaviors. Quantitative analysis of cross-system, administrative data of 7th grade students in the state of Minnesota found that Black girls were overrepresented in OSS relative to white, Asian, and Hispanic boys and girls, and Native girls. Furthermore, Black girls were sanctioned more harshly than were white students for disruptive, disorderly and violent behaviors. Finally, qualitative data suggested strategies to reduce disproportionality in the frequency and severity of OSSs for Black girls. Educators, especially those in leadership roles, can work to eliminate sexual harassment and bullying experienced by Black girls; and create programs to build upon their self-advocacy such as developing supportive communities of other Black girls and trusted adults at school. Highlights: Out-of-school suspensions (OSSs) are a persistent multi-level social justice and child well-being issue. Black girls were overrepresented in OSS relative to white, Asian, and Hispanic boys and girls, and Native girls. Black girls were sanctioned more harshly than were white students for certain behaviors. Black girls described OSSs as unfair, and forcefully defended themselves. Educators can work to create programs to build upon their self-advocacy.